(untitled) (Bangladesh Journal of Medical Science, 2011)
Objectives: The study was undertaken to explore the effects of prepregnancy body mass index (BMI) and excess weight gain on maternal and neonatal outcomes different maternal and neonatal outcomes. Methods: Obstetrics records of 496 singleton pregnant women delivered between 2007 and 2009 in IBN SINA Medical College Hospital were reviewed. On the basis of BMI on their first visit the patients were divided into 3 groups; Mat BMI Gr 1, normal (BMI 20–24.9 Kg/m2, n=366), Mat BMI Gr 2, overweight (BMI 25-29.9 Kg/m2, n=102), Mat BMI Gr 3, obese (BMI >30 Kg/m2, n=28). On the basis of gestational weight gain, the subject divided into 2 categories, Gets WtGain Gr A, gestational weight gain 8–15.9 Kg (n=315), Gest WtGain Gr B, gestational weight gain >16 Kg weight gain (n=181). Data were expressed as number (percentage). Proportion test was performed for comparison between two groups. P value <0.05 was taken as level of significance. Results: of the total 496 pregnant women 74.59% were between 19-34 years of age. Among all the women 64.11% had high school education of different grade. Of all the pregnancies 23.18% were nulliparous. Of the total 496 women 366 (79.79%) were normal weight, 102 (20.56%) overweight and 28 (5.64%) obese. Obese women group had significantly higher proportion of hypertensive cases compared to the normal weight (p<0.001) and overweight (p<0.01) group. Relatively higher proportion of macrosomia, birth trauma, shoulder dystocia and NICU admission among babies of obese women (p=ns). One hundred and eighty one (36.49%) of study subjects had gestational weight gain above the cut-off (>16 kg) value (p<0.001). Women with weight gain bout the cut-off level had relatively higher proportion of macrosomic babies (p=ns). Conclusions: The data reconfirmed that obesity is associated with hypertension. Significant proportion of women had weight gain more than cut-off value which needs to be addressed to ensure sound maternal and fetal wellbeing. However, a multicentre large scale study is warranted which may help the researchers to conclusively comment on the issue and thus plan future strategies for health care during pregnancy. Key words: Pre-pregnancy body mass index, gestational weight gain, obstetrics outcomes. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8364 BJMS 2011; 10(3): 195-199